a-Factor from Saccharomyces cerevisiae: partial characterization of a mating hormone produced by cells of mating type a. - Betz, R (1977)
Conjugation between haploid cells of Saccharomyces cerevisiae is mediated through the action of diffusible mating hormones, two of which have been designated as a-factor and alpha-factor. Partially purified fractions exhibiting a-factor activity have been obtained from culture filtrates of a cells by ultrafiltration, ion-exchange chromatography, and gel filtration. The a-factor preparations specifically caused both G1 arrest and morphological alterations in cells of alpha-mating type, whereas a cells, a/alpha diploids, and nonmating alpha mutants were not affected. The a-factor activity was found in the culture filtrates of all a strains tested, but not in filtrates of alpha or a/alpha cell cultures. The hormone is sensitive to various proteases, showing that it is associated with a peptide or protein. Gel filtration studies suggest an apparent molecular weight greater than 600,000; however, this result may be due to aggregation with carbohydrate present in the preparations. Although the biological activities of a-factor are analogous to those described previously for alpha-factor, the chemical properties of these two hormones appear to be quite different.